2002
DOI: 10.1029/2001ja000500
|View full text |Cite
|
Sign up to set email alerts
|

Sunspot activity and the long‐term variation of the Sun's open magnetic flux

Abstract: [1] The interplanetary magnetic field (IMF) originates in open magnetic regions of the Sun (coronal holes), which in turn form mainly through the emergence and dispersal of active region fields. The radial IMF strength is proportional to the total open flux È open , which can be estimated from source surface extrapolations of the measured photospheric field, after correction for magnetograph saturation effects. We derive the long-term variation of È open during 1971-2000 and discuss its relation to sunspot ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 38 publications
5
65
0
Order By: Relevance
“…With an improved latitudedependent saturation correction factor, Wang and Sheeley (1995) were able to match to the radial field seen at Earth during solar cycles 20 and 21, again using the assumption that B r is independent of latitude in the heliosphere, as found from the Ulysses observations. Recently, Wang and Sheeley (2002) have shown that this result holds for cycles 22 and 23 as well. Thus, the work of Sheeley (1995, 2002) gives strong evidence that the Ulysses result on the uniformity of the radial heliospheric field is valid throughout cycles 21-23.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…With an improved latitudedependent saturation correction factor, Wang and Sheeley (1995) were able to match to the radial field seen at Earth during solar cycles 20 and 21, again using the assumption that B r is independent of latitude in the heliosphere, as found from the Ulysses observations. Recently, Wang and Sheeley (2002) have shown that this result holds for cycles 22 and 23 as well. Thus, the work of Sheeley (1995, 2002) gives strong evidence that the Ulysses result on the uniformity of the radial heliospheric field is valid throughout cycles 21-23.…”
Section: Introductionmentioning
confidence: 67%
“…(1). The PFSS procedure, as applied by Wang and Sheeley (2002) were used. The first perihelion pass took place during the interval September 1994 until July 1995 and thus, the [F s ] PFSS value in Table 1 , Lockwood et al 1999aLockwood, 2001Lockwood, , 2002b, agrees well with the predictions of the modelling by Solanki et al (2000) and Lean et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mackay et al concluded that something important must be missing from the model and suggested that the problem might lie with the source-surface component. However, the source-surface model seems to be an unlikely culprit because it correctly reproduces the observed variation of open flux when it is applied to the observed photospheric field (as opposed to the field simulated from the doublet sources) (Wang et al, 2000a;Wang and Sheeley Jr, 2002).…”
Section: Living Reviews In Solar Physicsmentioning
confidence: 99%
“…The author pointed out that the correction factor used by Wang & Sheeley [50] was only correct for the use on MWO data and did not apply to WSO data. It has its own correction factor of 1.85 [52].…”
Section: (I) Magnitude Variation Modelsmentioning
confidence: 99%
“…In the study by Wang & Sheeley [50], a combination of synoptic magnetograms and PFSS models were used to compute the open flux from 1971 to 1998. The synoptic magnetograms originated from either Wilcox Solar Observatory (WSO 1976(WSO -1995 or Mount Wilson Observatory (MWO 1971(MWO -1976(MWO , 1995(MWO -1998.…”
Section: (I) Magnitude Variation Modelsmentioning
confidence: 99%